On integrated wheel and track damage prediction using vehicle–track dynamic simulations. (August 2017) - Casanueva, Carlos; Enblom, Roger; Stichel, Sebastian; Berg, Mats
The renewal costs for wheels and rails are a substantial part of the costs for rolling stock operators and infrastructure managers all over the world. The causes for reprofiling or grinding are, in most cases, related to the following: (1) wheel or rail profiles with unacceptable wear, (2) appearance of rolling contact fatigue cracks in the surface, and (3) wheel flats caused by locking wheels during braking. The first two causes are related to the dynamic behavior of the vehicle–track system, and can be predicted using multibody simulations. However, there are several limitations that restrain the usefulness of these prediction techniques, such as simulation time constraints, necessary simplifications, and lack of experimental data that lead to educated assumptions. In this paper, we take the end-user perspective in order to show whether the latest developments in wheel–rail damage prediction can be integrated in a simplified framework, and subsequently used by the different stakeholders for an improved management of the different assets involved in the operation of rail vehicles.